TECHNOLOGICAL PECULIARITIES O F MELTING AND OUT-OF-FURNACE PROCESSING OF BALANCED STEELS IN CONDITIONS OF ELECTRIC FURNACE STEELMAKING AND CONTINUOUS CASTING - S. V. Terletski; V. V. Pivtsajev; A. V. Olenchenko; A. S. Zazjan (Литьë и металлургия)
The technological peculiarities of melting and out-of-furnace processing of balanced steels in conditions of electric furnace steelmaking and continuous cast of RUP “BMZ” are considered.